2016
DOI: 10.1016/j.bbi.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Histamine regulation of microglia: Gene-environment interaction in the regulation of central nervous system inflammation

Abstract: Microglia mediate neuroinflammation and regulate brain development and homeostasis. Microglial abnormalities are implicated in a range of neuropsychiatric pathology, including Tourette syndrome (TS) and autism. Histamine (HA) is both a neurotransmitter and an immune modulator. HA deficiency has been implicated as a rare cause of TS and may contribute to other neuropsychiatric conditions. In vitro studies suggest that HA can regulate microglia, but this has never been explored in vivo. We used immunohistochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 70 publications
4
68
0
Order By: Relevance
“…We have described complex abnormalities of microglia in a mouse model of Tourette syndrome [46]. Naïve Hdc-KO mice display morphological abnormalities in striatal microglia that suggest quiescence, normal expression of inflammatory markers, but a reduced number of IGF-1 expressing microglia.…”
Section: Possible Mechanismsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have described complex abnormalities of microglia in a mouse model of Tourette syndrome [46]. Naïve Hdc-KO mice display morphological abnormalities in striatal microglia that suggest quiescence, normal expression of inflammatory markers, but a reduced number of IGF-1 expressing microglia.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…We found that microglia cells are not activated in basal conditions in the striatum in Hdc -KO mice; rather, microglia from this mice exhibit reduced arborization and normal expression of inflammatory markers [46]. A similar effect is seen when neuronally derived histamine is specifically disrupted, through targeted virus-mediated ablation of histaminergic neurons in the posterior hypothalamus [46]. The total number of microglia is unchanged in KO animals, but the number of microglia expressing Insulin-like Growth Factor 1 (IGF-1) is reduced.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations